Peran Program PMT Terhadap Pengentasan Stunting Di Pedesaan - Ibnu Phonna Nurdin; Wilda Miska Raihani; Mustaqim (Indo Publishing, 2025)
Stunting remains one of the most pressing nutritional challenges worldwide, including in Indonesia, which ranks second in Southeast Asia and fifth globally in terms of child stunting prevalence. In Aceh Besar District, the stunting rate has reached 16.2%, prompting the government to implement several intervention programs, including the Supplementary Feeding Program (PMT). This study aims to analyze the role of the PMT in reducing stunting in Gampong Tanjong Selamat. Using George Herbert Mead’s role theory as the analytical framework, this research adopts a qualitative case study approach. The data were collected through observation, in-depth interviews, and documentation. Informants included PMT coordinators and cadres, parents of stunted children, as well as key informants such as the village head (Keuchik) and youth leader. The findings indicate that PMT cadres perform two essential roles: socialization and nutritional intervention. However, the implementation of the program faces several limitations, including inadequate timing of outreach activities, lack of interactive engagement during health education sessions, suboptimal nutritional content of the meals provided, and the absence of pediatric specialists in treating stunted children. The study concludes that while the PMT program contributes positively to addressing stunting, its overall impact is constrained by operational and structural gaps. Strengthened support from local health authorities and improved inter-sectoral coordination are needed to enhance the effectiveness and sustainability of stunting eradication efforts in the region.